A human induced pluripotent stem cell model from a patient with hereditary cerebral small vessel disease carrying a heterozygous R302Q mutation in HTRA1 - Qian, Emi; Uemura, Masahiro; Kobayashi, Hiroya; Nakamura, Shiho; Ozawa, Fumiko; Yoshimatsu, Sho; Ishikawa, Mitsuru; Onodera, Osamu; Morimoto, Satoru; Okano, Hideyuki (Inflammation and Regeneration, 2023)
Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is an inherited cerebral small vessel disease (CSVD) caused by biallelic mutations in the high-temperature requirement serine peptidase A1 (HTRA1) gene. Even heterozygous mutations in HTRA1 are recently revealed to cause cardinal clinical features of CSVD. Here, we report the first establishment of a human induced pluripotent stem cell (hiPSC) line from a patient with heterozygous HTRA1-related CSVD. Peripheral blood mononuclear cells (PBMCs) were reprogrammed by the transfection of episomal vectors encoding human OCT3/4 (POU5F1), SOX2, KLF4, L-MYC, LIN28, and a murine dominant-negative mutant of p53 (mp53DD). The established iPSCs had normal morphology as human pluripotent stem cells and normal karyotype (46XX). Moreover, we found that the HTRA1 missense mutation (c.905G>A, p.R302Q) was heterozygous. These iPSCs expressed pluripotency-related markers and had the potential to differentiate into all three germ layers in vitro. HTRA1 and the supposed disease-associated gene NOG were differentially expressed in the patient iPSCs at mRNA levels compared to those of control lines. The iPSC line would facilitate in vitro research for understanding the cellular pathomechanisms caused by the HTRA1 mutation including its dominant-negative effect.